Dyshormonogenetic goiter with papillary hyperplasia mimicking papillary carcinoma: A rare entity (Indian Journal of Case Reports, 2026)
Dyshormonogenetic goiter is a rare genetically determined thyroid hyperplasia that causes congenital hypothyroidism. It occurs due to a lack of enzymes necessary for the synthesis of thyroid hormones. It is morphologically characterized by architectural and cellular pleomorphism that may mimic thyroid malignancy and cause difficulties in differential diagnosis. It occurs due to mutations in genes encoding enzymes, which participate in thyroid hormone synthesis. This is a case report of a 34-year-old male who presented with slow-growing right neck swelling for the past 5 years. Ultrasonography of the neck showed TIRAD 4 nodules, and the lesion was diagnosed as dyshormonogenetic goiter microscopically. The focal area showed papillary hyperplasia mimicking papillary carcinoma of the thyroid (PCT). Immunohistochemistry was done, and the possibility of PCT was ruled out.